B-Mode Gray Scale Ultrasound of the Head in the Newborn and Young Infant - Babcock, Diane S.; Han, Bokyung K.; LeQuesne, Garry W. (American Journal of Neuroradiology, 1980)
A technique using commercially available B-mode gray scale ultrasonography for imaging the head in the newborn and young infant is described. Serial scans were performed at several angles from the canthomeatal line. Images of technical quality previously unobtainable are shown. Normal anatomic structures such as ventricles, cerebral peduncles, pons, cerebellum, sulci, gyri, choroid plexus, falx cerebri, and tentorium cerebelli can be demonstrated. From April 1978 through December 1978, 165 gray scale ultrasonograms of the head on 111 children younger than 2 years were performed; 63 normal and 48 abnormal patients were studied, with hydrocephalus of various etiologies the most common abnormality. Porencephalic cysts, developmental anomalies, intraventricular and intracerebral hemorrhages, cephalohematoma, subdural hematomas, and arteriovenous malformations were demonstrated. Because of its safety and relatively low cost, ultrasonography proved to be an excellent method for following ventricular size and shunt function.